Functional evaluation of elderly attended in Primary Care (Research, Society and Development, 2022)
Objectives: to estimate the prevalence of functional incapacity for basic and instrumental activities of daily living and its association with socioeconomic, demographic and health characteristics in the elderly. methodology: a semi-structured questionnaire was requested to collect sociodemographic data, obtained through the katz and lawton scales, and mobility was also assessed through the test time get up and go test. results: outcome the study consisted of 15 men and 28 women. we had a predominance of elderly people aged between 60 and 69 years old and married. higher prevalence of low education, retirees and farmers. systemic arterial hypertension was the most prevalent disease. the highest percentage of elderly people is assisted by a doctor, nursing and responsible health agents. in the evaluation of the katz scale, it is shown to be independent. on the lawton scale, 87% of men and 86% of women are independent. as for the risk of falls, 76.7% of the elderly were at medium risk. conclusion: all the objectives imposed in this research were clearly achieved and when observing all these findings, it would be extremely important to apply a physical therapy exercise protocol for these elderly people.